Method for efficiently preparing SiC fibers through airflow-assisted electrostatic spinning
Through airflow-assisted electrospinning process and improved spinning liquid components, the problems of low efficiency and single fiber morphology of traditional SiC fiber preparation methods are solved, and SiC fibers with high efficiency preparation and high thermal insulation performance are achieved.
Patent Information
- Application Number
- CN202411517474.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The traditional SiC fiber preparation method is cumbersome, the preparation efficiency is low, and electrospinning technology has shortcomings in the supply rate of spinning liquid and the diversity of fiber morphology.
The airflow-assisted electrospinning process is used to improve the spinning liquid components, add polyvinylpyrrolidone and sodium dodecyl sulfate, and use a receiver with a specific structure to improve the spinning efficiency and fiber thermal insulation performance.
It significantly improves the preparation efficiency of SiC fibers, maintains high thermal insulation performance, and reduces the phenomenon of droplets aggregation of needles during spinning, and improves the smoothness of spinning process.
Smart Images

Figure CN119392408A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to a method for efficiently preparing SiC fibers through airflow-assisted electrostatic spinning. Background Art
[0002] Silicon carbide (SiC) fiber is a high-performance ceramic material with advantages such as high temperature oxidation resistance, high hardness, high strength, high thermal stability, corrosion resistance and low density. Under extreme conditions, SiC fiber can maintain good performance compared to traditional fiber materials such as carbon fiber. Traditional methods for synthesizing SiC fibers include vapor phase growth method (such as chemical vapor deposition method) and liquid phase growth method (such as solvent thermal method), but these methods are cumbersome and have relatively low preparation efficiency, and are not suitable for large-scale preparation of SiC fibers.
[0003] Electrospinning technology is a technology that uses the jet flow formed between electrodes under the action of an electric field to quickly spin polymer solutions. It has the advantages of simple principle and relatively high production efficiency. In recent years, traditional electrospinning technology has been used to prepare SiC fibers, which has improved the preparation efficiency of SiC fibers to a certain extent. However, the supply rate of the spinning solution during the preparation process is only 2mL, and the efficiency is still not high enough. And because a single drum receiver is used, the morphology of the spun fibers is also relatively simple, with only a membrane structure, which is also a problem with most current electrospinning technologies. At the same time, when spinning with traditional formulas, the spinning process is greatly affected by humidity, and the spinning solution has poor conductivity, resulting in condensed droplets often appearing on the needle during the spinning process to block the spinning process. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a method for efficiently preparing SiC fibers by airflow-assisted electrospinning, which adopts an airflow-assisted electrospinning process, improves the composition of the spinning solution, and adopts a receiver with a specific structure, so that the spinning efficiency is greatly improved while the fiber still maintains high thermal insulation performance.
[0005] In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing SiC fiber, comprising the following steps:
[0006] (1) dissolving polycarbosilane in a mixed solvent, adding polyvinyl pyrrolidone and sodium dodecyl sulfate, and mixing to obtain a spinning solution; the mixed solvent comprises ethanol and tetrahydrofuran;
[0007] (2) electrospinning the spinning solution using an airflow-assisted electrospinning process to obtain a spinning product;
[0008] (3) After drying the spinning product, heating pre-oxidation and calcination are performed in sequence to obtain the SiC fiber.
[0009] Specifically, when preparing the SiC fiber of the present invention, a spinning solution of a specific component is used for electrostatic spinning, and an airflow-assisted process is used to greatly improve the preparation efficiency of the SiC fiber. The present invention uses polycarbosilane as a precursor of the SiC fiber, ethanol and tetrahydrofuran as a mixed solvent, and adds a certain amount of sodium dodecyl sulfate and polyvinyl pyrrolidone as a spinning solution; sodium dodecyl sulfate is directly added to the spinning solution, ethanol and tetrahydrofuran can help dissolve the sodium dodecyl sulfate, and the part exceeding the solubility forms a suspension, which directly promotes the improvement of the conductivity of the spinning line liquid, thereby improving the spinning efficiency. At the same time, the addition of sodium dodecyl sulfate can also effectively reduce the needle tip aggregation droplets during the electrostatic spinning process, prevent the phenomenon of spinning interruption, improve the smoothness of the spinning process, and further improve the spinning efficiency.
[0010] In some embodiments of the present invention, in step (1), the volume ratio of ethanol to tetrahydrofuran is 1:(3-6). Preferably, the volume ratio of ethanol to tetrahydrofuran is (1.5-2):(7.5-8).
[0011] In some embodiments of the present invention, in step (1), the mass volume ratio of the polycarbosilane to ethanol is (0.5-1.5) g: 1 mL. Preferably, the mass volume ratio of the polycarbosilane to ethanol is (1.6-1.9) g: (1.5-2) mL.
[0012] In some embodiments of the present invention, in step (1), the mass ratio of polycarbosilane, polyvinyl pyrrolidone and sodium dodecyl sulfate is (3-7):1:(0.1-0.4). Preferably, the mass ratio of polycarbosilane, polyvinyl pyrrolidone and sodium dodecyl sulfate is (1.6-1.9):(0.3-0.5):(0.07-0.12).
[0013] In some embodiments of the present invention, in step (1), the mixing is performed by stirring at a rotation speed of 300-400 r / min for 3-7 days.
[0014] In some embodiments of the present invention, in step (2), the parameters of the airflow-assisted electrospinning process are: spinning voltage 20-30 kV, distance between receiver and needle 10-17 cm, gas flow 2-8 L / min, liquid supply rate 12-20 mL / min, and humidity 30-50%.
[0015] Specifically, the present invention adopts a spinning solution of specific components and performs electrostatic spinning with the assistance of a high-speed airflow, so that the liquid supply rate can reach up to 20 mL / min, greatly improving the spinning efficiency.
[0016] In some embodiments of the present invention, in step (2), the needle for the airflow-assisted electrospinning is a 21-23G flat-mouth needle.
[0017] In some embodiments of the present invention, in step (2), the receiver has a curved grid structure. Preferably, the receiver is in a curved arc shape and is composed of a metal grid, and the curvature of the metal grid is 140-170°.
[0018] Specifically, a grid-shaped special-shaped receiver is used. During the spinning process, the fibers tend to be arranged along the conductive grid, while the fibers are arranged irregularly in the gaps of the grid. Thus, a fiber membrane with an uneven "skeleton structure" is prepared, resulting in different density areas in the fiber membrane. While the spinning efficiency is greatly improved, the fiber still maintains a high thermal insulation performance.
[0019] In some embodiments of the present invention, in step (3), the temperature regime of the heating pre-oxidation is: firstly, heating to 100-120°C at a rate of 1-3°C / min, and keeping warm for 3-5 hours; then heating to 130-150°C at a rate of 0.6-0.8°C / min, and keeping warm for 1-3 hours; then heating to 180-190°C at a rate of 0.3-0.5°C / min, and keeping warm for 1-3 hours; finally, cooling naturally to room temperature. The spinning product is subjected to segmented heating pre-oxidation to ensure that the long chains of polycarbosilane are fully reacted at different temperatures, thereby completely softening the polycarbosilane.
[0020] In some embodiments of the present invention, in step (3), the calcination temperature system is: first, vacuum heating to 280-320°C at a rate of 4-6°C / min, and nitrogen with a flow rate of 5-10L / min is introduced; continue to heat to 440-460°C at a rate of 4-6°C / min, and keep warm for 2-4 hours; then heat to 580-620°C at a rate of 2-4°C / min, and keep warm for 2-3 hours; continue to heat to 780-820°C at a rate of 2-4°C / min, and keep warm for 2-3 hours; finally, heat to 1100-1300°C at a rate of 2-4°C / min, and keep warm for 1-2 hours. The present invention adopts a staged heating system and keeps warm for a certain period of time, and its main purpose is: at low temperature, the organic components (such as polyvinyl pyrrolidone) in the fiber are completely decomposed; at high temperature, the fiber is completely thermally cracked, thereby further improving the comprehensive properties of the fiber.
[0021] A second aspect of the present invention provides a SiC fiber, wherein the SiC fiber is prepared by the above method, and the high temperature diffusion coefficient of the SiC fiber is less than 0.6 mm 2 / s.
[0022] The third aspect of the present invention provides the use of the above-mentioned SiC fiber in aerospace, nuclear energy, high-temperature gas turbines, metal-based or ceramic-based composite materials.
[0023] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0024] Compared with the traditional electrospinning process, the method for preparing SiC fiber of the present invention adopts a spinning solution of specific components, polycarbosilane as the precursor of SiC fiber, ethanol and tetrahydrofuran as a mixed solvent, and a certain amount of sodium dodecyl sulfate and polyvinyl pyrrolidone are added, and sodium dodecyl sulfate is used to improve the conductivity of the spinning solution, and reduce the needle droplets gathered during the electrospinning process, thereby improving the smoothness of the spinning process and improving the spinning efficiency; on the other hand, high-speed airflow is introduced to assist the spinning, and the spinning is operated at a higher liquid supply rate, which greatly improves the spinning efficiency. At the same time, the present invention adopts a grid-shaped special-shaped receiver, and the fibers tend to be arranged along the conductive grid during the spinning process, while the fibers are arranged irregularly in the gaps of the grid, thereby preparing a fiber membrane containing a "skeleton structure". While the spinning efficiency is greatly improved, the fiber still retains a high thermal insulation performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A physical picture of the spinning receiver used in the present invention;
[0026] Figure 2 This is a physical picture of the SiC fiber prepared in Example 1;
[0027] Figure 3 This is a diagram showing the phenomenon of needle-head aggregation of droplets when preparing SiC fiber in Comparative Example 1;
[0028] Figure 4 This is a physical picture of the SiC fiber prepared in Comparative Example 3;
[0029] Figure 5 XRD patterns of SiC fibers prepared in Examples 1-3;
[0030] Figure 6 This is a SEM image of the "skeleton" of the SiC fiber prepared in Example 1;
[0031] Figure 7 The thermal diffusion coefficient curve of SiC fibers prepared in Examples 1-3. DETAILED DESCRIPTION
[0032] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0033] Example 1
[0034] A method for efficiently preparing SiC fibers by airflow-assisted electrospinning comprises the following steps:
[0035] (1) Preparation of spinning solution: 1.6 g of pure polycarbosilane was dissolved in a mixed solvent of 2 mL of ethanol and 7.8 mL of tetrahydrofuran, and 0.35 g of polyvinyl pyrrolidone (mW=1300000) and 0.07 g of sodium dodecyl sulfate were added; the mixture was stirred at a speed of 350 r / min for 4 days to obtain a spinning solution.
[0036] (2) Electrospinning: The spinning solution prepared in step (1) is loaded into a 10 mL syringe and loaded with a 21G flat-blade needle with an airflow assist device. The syringe and the spinning receiver with a curved grid structure are then placed in a spinning device to perform airflow-assisted electrospinning to obtain a spinning product.
[0037] The parameters of the airflow-assisted electrospinning process are as follows: spinning voltage 22 kV, distance between the receiver and the needle 15 cm, gas flow rate 2 L / min, liquid supply rate 12 mL / min, and humidity 30%.
[0038] The actual spinning receiver Figure 1 As shown, the spinning receiver is in a curved arc shape and is composed of a metal grid, and the curvature of the metal grid is 140°.
[0039] (3) Pre-oxidation: The spinning product obtained in step (2) is removed from the receiver, placed on a ceramic tray and dried in an oven at 60°C for 30 minutes; the dried raw silk is then transferred to an oven with a controllable heating program for heating pre-oxidation.
[0040] The temperature system of heating pre-oxidation is as follows: first, the temperature is increased to 110°C at a rate of 1.8°C / min and kept at this temperature for 3 hours; then, the temperature is increased to 140°C at a rate of 0.8°C / min and kept at this temperature for 2 hours; then, the temperature is increased to 185°C at a rate of 0.4°C / min and kept at this temperature for 2 hours; finally, the temperature is naturally cooled to room temperature.
[0041] (4) Calcination: The raw fibers pre-oxidized in step (3) are placed in a graphite vacuum furnace for calcination to obtain the SiC fibers of this embodiment.
[0042] The calcination temperature regime is as follows: first, heat to 300°C in vacuum at a rate of 5°C / min, and introduce nitrogen at a flow rate of 7L / min; continue to heat to 450°C at a rate of 3°C / min, and keep warm for 3 hours; then heat to 600°C at a rate of 3°C / min, and keep warm for 2 hours; then heat to 800°C at a rate of 3°C / min, and keep warm for 2 hours; then heat to 1100°C at a rate of 3°C / min, and keep warm for 1 hour.
[0043] Figure 2 This is a physical picture of the SiC fiber prepared in this embodiment, wherein: Figure 2 -B is Figure 2 -A partial enlargement. Figure 2 It can be seen that the surface of the SiC fiber is grid-like, which is similar to the grid structure of the spinning receiver.
[0044] Example 2
[0045] A method for efficiently preparing SiC fibers by airflow-assisted electrospinning comprises the following steps:
[0046] (1) Preparation of spinning solution: 1.7 g of pure polycarbosilane was dissolved in a mixed solvent of 2 mL of ethanol and 8 mL of tetrahydrofuran, and 0.36 g of polyvinyl pyrrolidone (mW=1300000) and 0.1 g of sodium dodecyl sulfate were added; the mixture was then stirred at a speed of 400 r / min for 4 days to obtain a spinning solution.
[0047] (2) Electrospinning: The spinning solution prepared in step (1) is loaded into a 10 mL syringe and loaded with a 21G flat-blade needle with an airflow assist device. The syringe and the spinning receiver with a curved grid structure are then placed in a spinning device to perform airflow-assisted electrospinning to obtain a spinning product.
[0048] The parameters of the airflow-assisted electrospinning process are as follows: spinning voltage 24 kV, distance between the receiver and the needle 15 cm, gas flow 4 L / min, liquid supply rate 15 mL / min, and humidity 30%.
[0049] (3) Pre-oxidation: The spinning product obtained in step (2) is removed from the receiver, placed on a ceramic tray and dried in an oven at 60°C for 30 minutes; the dried raw silk is then transferred to an oven with a controllable heating program for heating pre-oxidation.
[0050] The temperature system of heating pre-oxidation is as follows: first, the temperature is increased to 110°C at a rate of 1.8°C / min and kept at this temperature for 3 hours; then, the temperature is increased to 140°C at a rate of 0.8°C / min and kept at this temperature for 2 hours; then, the temperature is increased to 185°C at a rate of 0.4°C / min and kept at this temperature for 2 hours; finally, the temperature is naturally cooled to room temperature.
[0051] (4) Calcination: The raw fibers pre-oxidized in step (3) are placed in a graphite vacuum furnace for calcination to obtain the SiC fibers of this embodiment.
[0052] The calcination temperature regime is as follows: first, heat to 300°C in vacuum at a rate of 5°C / min, and introduce nitrogen at a flow rate of 8 L / min; continue to heat to 450°C at a rate of 3°C / min, and keep warm for 3 hours; then heat to 600°C at a rate of 3°C / min, and keep warm for 2 hours; then heat to 800°C at a rate of 3°C / min, and keep warm for 2 hours; then heat to 1300°C at a rate of 3°C / min, and keep warm for 1 hour.
[0053] Example 3
[0054] A method for efficiently preparing SiC fibers by airflow-assisted electrospinning comprises the following steps:
[0055] (1) Preparation of spinning solution: 1.7 g of pure polycarbosilane was dissolved in a mixed solvent of 2 mL of ethanol and 8 mL of tetrahydrofuran, and 0.36 g of polyvinyl pyrrolidone (mW=1300000) and 0.1 g of sodium dodecyl sulfate were added; the mixture was then stirred at a speed of 400 r / min for 4 days to obtain a spinning solution.
[0056] (2) Electrospinning: The spinning solution prepared in step (1) is loaded into a 10 mL syringe and loaded with a 21G flat-blade needle with an airflow assist device. The syringe and the spinning receiver with a curved grid structure are then placed in a spinning device to perform airflow-assisted electrospinning to obtain a spinning product.
[0057] The parameters of the airflow-assisted electrospinning process are as follows: spinning voltage 24 kV, distance between the receiver and the needle 15 cm, gas flow 4 L / min, liquid supply rate 20 mL / min, and humidity 50%.
[0058] (3) Pre-oxidation: The spinning product obtained in step (2) is removed from the receiver, placed on a ceramic tray and dried in an oven at 60°C for 30 minutes; the dried raw silk is then transferred to an oven with a controllable heating program for heating pre-oxidation.
[0059] The temperature system of heating pre-oxidation is as follows: first, the temperature is increased to 110°C at a rate of 1.8°C / min and kept at this temperature for 3 hours; then, the temperature is increased to 140°C at a rate of 0.8°C / min and kept at this temperature for 2 hours; then, the temperature is increased to 185°C at a rate of 0.4°C / min and kept at this temperature for 2 hours; finally, the temperature is naturally cooled to room temperature.
[0060] (4) Calcination: The raw fibers pre-oxidized in step (3) are placed in a graphite vacuum furnace for calcination to obtain the SiC fibers of this embodiment.
[0061] The calcination temperature regime is as follows: first, heat to 300°C in vacuum at a rate of 5°C / min, and introduce nitrogen at a flow rate of 8 L / min; continue to heat to 450°C at a rate of 3°C / min, and keep warm for 3 hours; then heat to 600°C at a rate of 3°C / min, and keep warm for 2 hours; then heat to 800°C at a rate of 3°C / min, and keep warm for 2 hours; then heat to 1200°C at a rate of 3°C / min, and keep warm for 1 hour.
[0062] Comparative Example 1
[0063] The difference between Comparative Example 1 and Example 1 is only that the components of the spinning solution are different. No sodium dodecyl sulfate is added to the spinning solution of Comparative Example 1. The preparation process is: 1.6 g of pure polycarbosilane is dissolved in a mixed solvent of 2 mL of ethanol and 7.8 mL of tetrahydrofuran, and 0.35 g of polyvinyl pyrrolidone (mW=1300000) is added; then the mixture is stirred at a speed of 350 r / min for 4 days to obtain the spinning solution.
[0064] Comparative Example 1 During the electrospinning process, the needle often accumulates droplets, such as Figure 3 As shown, the overall spinning process is not smooth, and the spinning needs to be interrupted frequently to manually remove the droplets, which greatly reduces the spinning efficiency.
[0065] Comparative Example 2
[0066] The difference between Comparative Example 2 and Example 1 is only that the components of the spinning solution are different. The spinning solution of Comparative Example 2 uses xylene as the solvent, and its preparation process is: 1.6g of pure polycarbosilane is dissolved in 9.8mL of xylene, 0.35g of polyvinyl pyrrolidone (mW=1300000) and 0.07g of sodium dodecyl sulfate are added; then stirred at a speed of 350r / min for 4 days. The experiment found that the xylene system spinning solution was not completely dissolved, and precipitation soon occurred after being loaded into the needle tube; during the spinning process, xylene could not evaporate quickly in the air, resulting in the fiber still being in liquid state when it reached the receiver, and it could not be successfully spun.
[0067] Comparative Example 3
[0068] The difference between Comparative Example 3 and Example 1 is only that the spinning receiver is different. The spinning receiver used in Comparative Example 3 is a traditional flat receiver without a grid structure. Figure 4 As shown, the fiber only has a membrane structure and does not have the skeleton structure of the fiber prepared in Examples 1-3, which is not conducive to the thermal insulation performance of the fiber.
[0069] Performance Testing
[0070] 1.XRD analysis
[0071] The fibers prepared in Examples 1-3 were ground into powder and subjected to XRD testing using a Bruker D8advance X-ray diffractometer. The test results are shown in FIG. Figure 5 As shown, where the horizontal axis 2theta represents the 2θ diffraction angle, and the vertical axis Intensity represents the intensity of the diffraction peak. Figure 5 It can be seen that when sintering at a lower temperature (1100°C), the degree of fiber crystallization is not high, but by sintering at a higher temperature (1300°C), the degree of fiber crystallization is greatly enhanced, and a typical SiC crystal diffraction peak appears.
[0072] 2. SEM analysis
[0073] Figure 6 This is the SEM image of the "skeleton" of the SiC fiber prepared in Example 1. Figure 6 A and Figure 6 B are microstructure images at different magnifications, and the equipment used is a Hitachi SU5000 thermal field emission scanning electron microscope. Figure 6 It can be seen that the fibers in the "skeleton" of the fiber membrane are arranged in the same direction, and the fiber density is significantly higher than that in other areas.
[0074] 3. Thermal diffusivity
[0075] The thermal diffusion coefficient of the SiC fibers prepared in Examples 1-3 was tested using a NETZSCH LFA467HT HyperFlash laser thermal conductivity instrument. The results are as follows: Figure 7 As shown, where the horizontal axis Temperature represents temperature and the vertical axis Diffusivity represents thermal diffusion coefficient. Figure 7 It can be seen that even if the sample is sintered at a lower temperature (1100°C), it still has a relatively low high-temperature thermal diffusion coefficient (<0.6 mm 2 / s); for samples sintered at a higher temperature (1300°C), the high temperature thermal diffusion coefficient is as low as 0.15 mm at 1000°C. 2 / s or less.
[0076] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A method for preparing SiC fiber, characterized in that: The following steps are involved: (1) dissolving polycarbosilane in a mixed solvent, adding polyvinyl pyrrolidone and sodium dodecyl sulfate, and mixing to obtain a spinning solution; the mixed solvent comprises ethanol and tetrahydrofuran; (2) electrospinning the spinning solution using an airflow-assisted electrospinning process to obtain a spinning product; (3) After drying the spinning product, heating pre-oxidation and calcination are performed in sequence to obtain the SiC fiber.
2. The method for preparing SiC fiber according to claim 1, characterized in that: In step (1), the volume ratio of ethanol to tetrahydrofuran is 1:(3-6); and / or the mass volume ratio of polycarbosilane to ethanol is (0.5-1.5) g:1 mL.
3. The method for preparing SiC fiber according to claim 1 or 2, characterized in that: In step (1), the mass ratio of the polycarbosilane, polyvinyl pyrrolidone and sodium dodecyl sulfate is (3-7):1:(0.1-0.4).
4. The method for preparing SiC fiber according to claim 1, characterized in that: In step (1), the mixing is carried out by stirring at a rotation speed of 300-400 r / min for 3-7 days.
5. The method for preparing SiC fiber according to claim 1, characterized in that: In step (2), the parameters of the airflow-assisted electrospinning process are: spinning voltage 20-30 kV, distance between receiver and needle 10-17 cm, gas flow 2-8 L / min, liquid supply rate 12-20 mL / min, and humidity 30-50%.
6. The method for preparing SiC fiber according to claim 5, characterized in that: In step (2), the receiver has a curved grid structure.
7. The method for preparing SiC fiber according to claim 1, characterized in that: In step (3), the temperature regime of the heating pre-oxidation is: firstly heating to 100-120°C at a rate of 1-3°C / min, and keeping warm for 3-5 hours; then heating to 130-150°C at a rate of 0.6-0.8°C / min, and keeping warm for 1-3 hours; then heating to 180-190°C at a rate of 0.3-0.5°C / min, and keeping warm for 1-3 hours; and finally naturally cooling to room temperature.
8. The method for preparing SiC fiber according to claim 1, characterized in that: In step (3), the calcination temperature regime is as follows: first, the temperature is raised to 280-320°C in vacuum at a rate of 4-6°C / min, and nitrogen is introduced at a flow rate of 5-10L / min; the temperature is further raised to 440-460°C at a rate of 4-6°C / min, and kept warm for 2-4 hours; the temperature is then raised to 580-620°C at a rate of 2-4°C / min, and kept warm for 2-3 hours; the temperature is further raised to 780-820°C at a rate of 2-4°C / min, and kept warm for 2-3 hours; and finally, the temperature is raised to 1100-1300°C at a rate of 2-4°C / min, and kept warm for 1-2 hours.
9. A SiC fiber, characterized in that: The SiC fiber is prepared by the method according to any one of claims 1 to 8, and the thermal diffusion coefficient of the SiC fiber is less than 0.6 mm 2 / s.
10. Use of the SiC fiber according to claim 9 in aerospace, nuclear energy, high temperature gas turbines, metal-based or ceramic-based composite materials.
Citation Information
Patent Citations
Preparation method for controllable patterned electrospinning fiber aggregate
CN102978720A
Airflow assisted electrostatic spinning nozzle and use method thereof
CN111005078A
Flexible silicon carbide fiber and preparation method thereof
CN112779631A
Bismuth oxide / gadolinium oxide nanofiber membrane alternately stacked composite material and preparation method thereof
CN115467091A
Elastic SiC ceramic sponge material as well as preparation method and application thereof
CN115557790A
Cited By
Amorphous silicon carbide fiber membrane prepared by precursor method as well as preparation method and application of amorphous silicon carbide fiber membrane
CN121204914A